Democracia e esportes em Atenas - Lessa, Fábio de Souza (2008)
In the commonsense among specialists there was a democratization in sports practice in the Classical Athens (centuries V and IV B.C.). That said, we suggest to study the relation between democracy and the dissemination of athletic practices in the Athenian polis, using athletic ´Çü gures from Greek vases as a form to explain this fact, such as the discobulos, which is considered as a symbol of the Athenian democracy.